Ultra High Temperature Rare Earth Metal Extraction By Electrolysis - Bradley R. Nakanishi; Guillaume Lambotte; Antoine Allanore (The Minerals, Metals and Materials Society, 2015)
Current industrial methods used for rare earth element (REE) extraction involve: 1) ore enrichment, 2) separation of rare earth oxides (REOs), 3) chlorination or hydrofluorination, and 4) individual electrowinning of REEs from a molten halide electrolyte. The complexity of REE extraction is inherited from their electronic configuration. Recently, molten oxide electrolysis (MOE) has been used to produce reactive metals directly from their oxides, e.g. titanium. As a single-step alternative to processes 3) and 4), or laboratory has investigated rare earth extraction by MOE. A key challenge is to find a molten electrolyte more stable than REOs. One possibility is to use binaries of REOs directly as a solvent. We have, therefore, developed two experimental approaches for studying molten REOs at temperatures exceeding 2200oC. The present work reports the most recent experimental results obtained with La2O3-Y2O3. Those promising results demonstrate potential for operating with molten REOs and refine the underlying materials challenge for electrodes to enable metal recovery.